(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Background: coronary artery disease is one of the most common types of cardiovascular disorder and it occurs when the coronary artery that supply blood to the heart muscle is compromised due to the accumulation of materials such as plaque/cholesterol atherosclerosis risk factors associated with coronary artery disease men are susceptible at 45, women at 55 include age, gender, genetics, etc, Objective: To identify the patients at elevated risk for CAD, To identify patients required further investigation to confirm the diagnosis of CAD, To describe a management plan including lifestyle changes, medications, psychosocial support, cardiac rehabilitation, etc. Methods: A prospective observational study was conducted for a period of 6 months, from CAD patients attending max cure hospital. The data was collected from the participants after consent. Relevant patient lifestyles and lab data were documented in the data collection form (DCF). Results: The study findings are according to parameter wise, age categorization defines that in 51-60 ranging age group 27.22% that is the highest percent affected people are observed with CAD. Of the total number of subjects participated in the study (n=202) the gender-wise comparison males (144) are more than females (58).To observe patient region, urban people (68%) are mostly affected with CAD than rural people (32%). To identify risk factors of CAD, patients with DM (34.67%), HTN (23%), smoking (17.32%), alcohol (25.74%), and obesity (13.86%) are the major risk factors associated with CAD. Based on family history a total of 21 members were identified out of 202, among them with CAD were 7, with CKD were 6, with HTN were 5 and with DM were 3 members respectively. According to the past history in a total of 202 members, patients with Cerebrovascular accidents were 4, patients with MI/UA were 20, and CKD were 4 respectively. Conclusion: Evaluation of risk factors in patients with coronary artery disease in a tertiary care hospital was observed. Age, Diabetes mellitus, Hypertension, Smoking, Alcohol, and Obesity are more causing risk factors than others.